Estimated divergence times of Hirsutella (asexual morphs) in Ophiocordyceps provides insight into evolution of phialide structure - Qu, Jiaojiao; Zhou, Yeming; Yu, Jianping; Zhang, Jian; Han, Yanfeng; Zou, Xiao (BMC evolutionary biology, 2018)
Hirsutella Pat genus, the asexual morphs of the Ophiocordyceps Sung, is globally distributed entomopathogenic fungi, which infect a variety of arthropods, mites and nematodes. The fungal species also have shown potential application in the field of biological control, bio-medicine and food development. Although these fungi are synonymized under Ophiocordyceps, formal taxonomic assignments remain necessary for classification of species in Hirsutella. However, due to the heterogeneity and complexity of Hirsutella genus, more detailed taxonomic and phylogenetic analyses are required to address the following subjects: (1) the relationships between the phialide morphological characteristics and phylogenetic information of Hirsutella with asexual morphs, (2) the origin and evolution of the phialide structure, and (3) host specificity and fungal pathogenicity. Five typical phialide structures are summarized, in which the variation in phialide characteristics overlaps well with phylogenetic information. A new member of the special twisted neck clade in the Hirsutella-like group, Ophiocordyceps retorta, was reported based on these analyses. The molecular clock calibration analysis based on one fossil record revealed that Hirsutella (asexual morph) species originated from a common ancestor approximately 102 million years ago (Mya) (Early Cretaceous, Lower Albian) and then resolved into two major lineages. One lineage was typically phialidic, which was a larger shape, including H. guyana, H. nodulosa and H. sinensis clades (86.9 Mya, 95% highest posterior density (HPD): 69.1-101.4 Mya). Another main lineage of the phialides was more diversified and smaller than the former, which included H. citriformis and H. thompsonii clades (71.9 Mya, 95% HPD: 41.8-99.6 Mya). Our results showed that certain phialide characteristics of Hirsutella were phylogenetically informative for two groups of taxa. The differentiation of the phialides structures in the major clades demonstrated a clear evolutionary path of Hirsutella (asexual morph) species, which exhibited two trends depending on the host size. Fungi in one of the groups displayed elongated conidiogenous cells with increased complexity of auxiliary structures from the mycelia. The species in another group reduced the volume of phialides and spores, which might be due to an energy-efficient strategy. These results suggested that a common origin allowed for diversification of given clades into separate niches. The distinct parallel evolutionary path combined with the specific phialides structure might result in the host specificity of Hirsutella (asexual morphs). A direct relationship between Hirsutella (asexual morphs) and the Cretaceous-Tertiary extinction was not found, which suggested that the diversity of phialides is more likely to be caused by long-term environmental adaptation and evolution rather than dramatic extinction events. This evolutionary result might correspond to the background of important biological and geological events in the late Cretaceous occurring near the divergence times of Hirsutella (asexual morphs).